(3GdHQeLI hGdJMdjd GdQjGVj (B:s (3JWHjbGJ Ydi GdGbJUGO (B/s - (3GdMeOGfj, QaGg TgGHs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2002)
(3jJfGhd gPG GdcJGH eSJhjGJ dZGJ GdHQeLI ceG jdj (B: (3GdebOeI(B-(3GdaUd GdChd (B: (3GdHQeLI hGdHQGeLjGJ (B: (3GdHQeLI HdZI GdeGcfI (B: (3dZGJ GdHQeLI (B: (3eSJhjGJ dZGJ GdHQeLI (B: (3GdeJQLeGJ (B: (3GdeaSQ (B: (3CfhGY GdHQGeLjGJ (B: (3Md GdeSGFd HhGSWI GdMGSHI (B: (3GdHQeLI dZI HGScGd (B: (3GdKhGHJ (B: (3GdeYQaGJ (B: (3GdYedjGJ GdQjGVjI (B: (3GdJYGHjQ GdQjGVjI(B-(3GdaUd GdKGfj (B: (3GdfeGPL GdGbJUGOjI heTcdI JhGRf GdGbJUGOj Gdbhej (B: (3GdfehPL GdGbJUGOj (B: (3GdfehPL GdGbJUGOj (B: (3GdfehPL GdSGcf dJhRGf GdGbJUGO Gdbhej (B: (3GdfeGPL GdMQcjI (B: (3fehPL GdJhGRf dGbJUGO bhej hab GdfeGPL GdMQcjI GdeJbWYI (B: (3eYGOdGJ GdaQhb (B: (3GdGfOQGL (B: (3GdGfOQGL GdNWj (B: (3GdGfOQGL aj eJYOO GdMOhO(B-(3GdaUd GdKGdK (B: (3Md efXheI GdfeGPL GdNWjI (B: (3GdMdhd GdYOOjI dCfXeI GdeYGOdGJ GdNWjI (B: (3WQjbI GdMPa dcGhS (B: (3Md efXheI GdeYGOdGJ GdNWjI HEjLGO eYchS eUahag GdeYGedGJ(B-(3GdaUd GdQGHY (B: (3Md GdeYGOdGJ ZjQ GdNWjI (B: (3GSJNGe GdQSe aj Md GdeYGOdGJ ZjQ GdNWjI (B: (3WQb Md GdeYGOdGJ ZjQ GdNWjI (B: (3GdMdhd GdYOOjI ddeYGOdGJ GdJaGVdjI GdGYJjGOjI(B-(3GdaUd GdNGeS (B: (3GdCSGdjH GdQjGVjI aj JMbjb GdcaGAI GdGbJUGOjI hJhGRf GdfXGe GdGbJUGOj (B: (3GdHQeLI GdNWjI (B: (3GdeSJNOe GdefJL (B: (3GdCSdhH GdbjGSj (B: (3GdHQeLI GddGNWjI(B.s
(3HjHdjhZQGajG U(B.187s
Keywords: (3GbJUGO QjGVjs; (3HQeLIs; (3JMdjd QjGVjs